Globalisasi perekonomian, sistem ekonomi nasional, dan otonomi daerah - Mardiasmo Mardiasmo (Economic Journal of Emerging Markets, 2000)
Indonesian government is facing two big challenges in this new era; those are global economic dependency and national economic system development. The former challenge is related to thechoices of economic systems orientation; and the latter, is related to the domestic society demands to develop new national economic system based on public interest or people-centered economy.